THE INFLUENCE OF UZBEK ON ENGLISH LANGUAGE LEARNING AMONG UZBEK SPEAKERS - Jabborov Manguberdi Murtazoyevich (Ustozlar uchun, 2025)
This article examines the impact of the Uzbek language on English language acquisition among Uzbek speakers, highlighting the linguistic, phonetic, grammatical and cultural issues. It discusses pronunciation difficulties such as the absence of certain English sounds in Uzbek, grammatical interference due to structural differences and vocabulary problems arising from direct translation and false cognates. In addition, the article discusses the cultural and cognitive factors that influence English language acquisition. By identifying these issues, the study suggests effective strategies to overcome them, including phonetic training, grammar exercises, vocabulary development and cultural immersion. The findings are useful for teachers and learners seeking to improve English language proficiency among Uzbek speakers.